2023
DOI: 10.3389/fimmu.2023.1152107
|View full text |Cite
|
Sign up to set email alerts
|

In sickness and in health: the dynamics of the fruit bat gut microbiota under a bacterial antigen challenge and its association with the immune response

Abstract: IntroductionInteractions between the gut microbiome (GM) and the immune system influence host health and fitness. However, few studies have investigated this link and GM dynamics during disease in wild species. Bats (Mammalia: Chiroptera) have an exceptional ability to cope with intracellular pathogens and a unique GM adapted to powered flight. Yet, the contribution of the GM to bat health, especially immunity, or how it is affected by disease, remains unknown.MethodsHere, we examined the dynamics of the Egypt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 85 publications
0
2
0
Order By: Relevance
“…In 2022 and 2023 Anne 65 and Tali et al 66 found that haptoglobin levels increased in Myotis myotis after stimulation by LPS, suggesting that haptoglobin is a major protein in bats during the acute inflammatory response period; Myotis myotis showed different haptoglobin hydroprotein levels in response to different stimuli, with haptoglobin levels decreasing after fungal infections and enzyme glycan attack resulting in a decrease of neutrophilic granulocytes were reduced; haptoglobin concentrations were also increased in LPS‐stimulated Rousettus aegyptiacus , possibly related to its own bacterial attack producing changes in gut microbial composition.…”
Section: Innate Immune Cells and Molecules In Batsmentioning
confidence: 99%
“…In 2022 and 2023 Anne 65 and Tali et al 66 found that haptoglobin levels increased in Myotis myotis after stimulation by LPS, suggesting that haptoglobin is a major protein in bats during the acute inflammatory response period; Myotis myotis showed different haptoglobin hydroprotein levels in response to different stimuli, with haptoglobin levels decreasing after fungal infections and enzyme glycan attack resulting in a decrease of neutrophilic granulocytes were reduced; haptoglobin concentrations were also increased in LPS‐stimulated Rousettus aegyptiacus , possibly related to its own bacterial attack producing changes in gut microbial composition.…”
Section: Innate Immune Cells and Molecules In Batsmentioning
confidence: 99%
“…Experimental studies have shown that GIT microbiota transplanted from great roundleaf bats ( Hipposideros armiger ) into antibiotic-treated mice altered immune cell levels and conferred greater resistance and survival to H1N1 influenza infection compared with control groups, indicating the GIT microbiome can interact with and change the host immune system [ 63 ]. Additionally, lipopolysaccharide injections in R. aegyptiacus induced significant and rapid (24–48 h) changes to the composition and diversity of gut microbial communities [ 64 ].…”
Section: Research At the Individual Scale: Metrics For Assessing Bat ...mentioning
confidence: 99%